Counsellors Respond to the DSM-IV-TR - Strong, Tom; Gaete, Joaquín; Sametband, Inés N.; French, Jared; Eeson, Jen (Canadian Journal of Counselling and Psychotherapy, 2012)
The Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) is an administrative fact for many counsellors. This psychiatric approach to formulating client concerns runs counter to those used by counsellors of many approaches (e.g., systemic, feminist). Using an online survey of counsellors (N = 116), invited contributions to a website blog, and in-depth interviews of 10 counsellors, we sought to better understand how the DSM-IV-TR infuenced counsellors' practice, and their responses to its expected use. From our situational analyses, we relate our findings to tensions experienced by counsellors when practicing from non-psychiatric approaches to practice.